Characterization Of Ti/TiN/AlCu Film Stack Prepared By Physical Vapor Deposition - Leow, Mun Tyng (2012)
Physical vapor deposition (PVD) method is widely used in semiconductor industry in metallic film deposition process. It has been found that the metallic film properties are influenced by the parameter change in the PVD sputtering machine. Ionized physical vapor deposition (I-PVD) came about when electronic devices shrink in sizes which increase the packing density of the device. This lead to higher aspect ratio of the via size and smaller interconnect lines of the integrated circuit. I-PVD sputtering method had successfully relieved the step coverage issues for high aspect ratio trenches and vias. In semiconductor industries, reliability surfaced as the major enemy.